Estratégias ativas para o ensino do sistema digestório: experiência com o Curso Técnico de Nutrição e Dietética - Pinheiro, Cinthya Rose Paulino Souza (2020)
It is inherent to Natural Sciences to reduce the distance between the student and scientific investigation scientific investigation, making them active in the search for strategies to solve problems. To this end,is essential to introduce diverse ways of teaching that meet the varied demands of the classroom, always taking into is essential to introduce diverse ways of teaching that meet the varied demands of the classroom, always taking into the classroom, always taking into consideration the equality of opportunities and equal rights. equal rights. At the same time, the organization of the classroom is often a challenge for the In parallel, the organization of the classroom is often a challenge for the Biology teacher, because in the same proportion that this demotivates many students. Recent studies show that inadequate methodologies in the teaching of anatomy and physiology of the digestive system result in lack of interest and absence construction of new knowledge. In this sense, an effective approach needs to foresee the construction of the problem and its introduction to the student, as well as to consider his prior knowledge applied to the problem, under the knowledge applied to the problem, under the mediation of the teacher. This research This research aimed to develop active and investigative didactic strategies for teaching the anatomy and and physiology of the digestive system and the feeding process in the second series of the medium level technical course in Nutrition and Dietetics of the Centro Estadual de Educação Profissional (CEEP) Professor João Faustino Ferreira Neto - Natal/RN. It was used as theoretical-methodological the quali-quantitative approach, and as methodology, the action research. methodology, the action research. Among the procedures carried out were: the participant observation of the classroom on a daily basis; a diagnostic questionnaire (used as a pre In addition, we used the following procedures: participant observation of the classroom on a daily basis; diagnostic questionnaire (used as a pre-test and post-test); audio and video recordings of the classes (with subsequent transcriptions); focal group; and miscellaneous field notes. The classes included discussions, practices and various experiences involving the contents of the digestive system, such as the use of concept concept maps, building three-dimensional models of organs, and comparing food labels, so that these activities These activities were performed as inquiry-based teaching. A use of these methodologies was effective during the teaching learning process because it minimized the difficulties of the student regarding the understanding and perception of his own body, in particular the structures that are part of the digestive system. In addition, the knowledge of students about the theme were re-signified, increasing the contribution of knowledge and of knowledge and the development of their skills. By correctly understanding the functioning of the digestive system, the students could also realize the importance of a healthy diet for the maintenance of the body's health status. As a product of the activities carried out, a Guide of Didactic Strategies for the Teaching of Anatomy and Anatomy and Physiology of the Digestive System and the Food Process, which will be available to teachers in the It will be available to teachers of Natural Sciences, especially those who teach Biology in High School. Biology at the High School level. Translated with www.DeepL.com/Translator (free version)